ANÁLISIS DE LA CALIDAD DEL SERVICIO DEL DEJA-VU RESTAURANTE & LOUNGE DE LA CIUDAD DE LOJA - Reyes Ordoñez, Karen Alexandra (2019)
The quality of the service towards a client is a fundamental strategy into the business relationships of any company. This quality with respect to the service corresponds to the satisfaction of the expectations from the users, a condition that is obtained when the perceptions are overcome after receiving a service. Within the tourism sector, restaurants are the main service companies. This is because they an intangible asset that is difficult to manage. But with the right management, it allows the success of any company. It becomes even more relevant when it is a high standard cuisine such as Deja-vu Restaurant & Lounge; considering that the restaurants in addition to offering the food and drink service provide a living experience where the gastronomy of the locality is shown, the culture of a town therefore helps endogenous development, becoming an instrument of marketing for tourism. In order to do this research entitled: "Analysis of the quality of the service of the Deja-vu Restaurant & Lounge of the City of Loja"; Firstly, it was ideal to make a diagnosis of the restaurant situation. After that, evaluate the quality of the service to the users through the Servqual method and finally strategies were proposed that aim to improve the quality of the service. During the diagnosis of the Restaurant, a matrix was applied based on the guidelines according to the requirements established for touristic places in Ecuador, perhaps as: Ministry of Tourism, Ministry of Labor, Ministry of the Environment, Police Administration-, CONADIS; ARCSA, SNDGR, ARCH, Municipality of Loja Then, the evaluation of the quality of the service was done by the Servqual technique which identified the index of quality of five dimensions such as: Reliability, Tangible Elements, Security, Empathy, Response Capacity and the unsatisfied needs of users based on expectations and perceptions. The proposed strategies were based on the results which 19% of users are not satisfied with the service, so the proposed strategies will cancel the unmet demand. For the elaboration of this research work it was necessary to use different methods such as deductive, descriptive hat were used during the realization of the first objective in the second objective, the analytical method served to determine each of the dimensions established in the Servqual method; In addition to some research techniques, direct observation, interview and survey were considered, which through their respective analysis and application allowed achieve the objectives set. 5 From the research it is concluded that in the Deja-vu Restaurant & Lounge of the City of Loja, 81% quality service can be found and to satisfy 19% of the unmet demand, the manager is advised to apply the proposed strategies coexisting with the need to increase demand through expectations and technological advances such as mobile applications for the exclusive use of users; when applying the letter in Braille System it is intended that the economic income increase, allowing the development of an inclusive tourism. It is worth mentioning that although there is a specific regulation for the food and beverages sector in Ecuador, which is not yet in force, as a result of which the decrease in tourism excellence at the territorial level with respect to this service has decreased; There is a lack of knowledge about the importance of tourism and the benefits that can be acquired from it.